Supervisi Akademik Kepala Madrasah Terhadap Optimalisasi Tugas Dan Fungsi Guru - Ramlan Ramlan; Farida Isroani (Pusat Riset dan Inovasi Nasional, 2022)
Academic supervision is one of the supervisions that must be carried out by the head of the madrasa to improve teacher performance, therefore, this thesis discusses the Academic Supervision Mechanism of the Head of Madrasah on Optimizing the Duties and Functions of the Teachers of Madrasah Ibtidaiyah Negeri 3 Lhokseumawe City. This study uses a descriptive qualitative approach. Data collection techniques with interview, observation and documentation methods. Data analysis techniques consist of (1) data reduction, (2) data presentation, and (3) conclusion drawing. With the research subject the Head of Madrasah and MIN 3 teachers in Lhokseumawe City. The results of this study are (1) academic supervision planning is arranged in prota and prosem. Optimizing the duties and functions of teachers by checking the lesson plans and the suitability of teaching methods, (2) the implementation of academic supervision is carried out with individual supervision techniques: class visits, observations and private conversations, and group supervision: meetings with teachers. (3) supervision of academic supervision in the form of supervision of supervision planning, supervision of the implementation of supervision and assessment. The findings in this study are that the academic supervision carried out by the madrasah principal produces results such as the teacher completing the teaching preparation (RPP), the teacher enters class according to the hour, and the teacher's activity in the classroom. Teachers who have problems in preparing lesson plans will be fostered and given training.